Allahmah ‘Abdul Hayy and His Works on Hadith Literature - Dr Muhammad Irshad-ul-Haq (Hazara Islamicus, 2013)
The ‘Ulam┐ ' of the Subcontinent India and Pakistan have always shown a considerable interest towards the diverse Islamic sciences and exerted great efforts for its conservation and development since centuries. There is no doubt that this fertile land has produced great ‘Ulam┐ ' who contributed to the Islamic sciences in a considerable manner. Their skill, vision, credit and contribution admired the whole Arab and Islamic world. Among these great genius scholars is Maul┐ na ‘Abdul ╓ ayy Firangi Mahall┘ , who has written hundreds of books on many Islamic sciences and most of them are in manuscript form, and his contribution to Islamic sciences in general and to ╒ ad┘ th literature and fiqh (Islamic jurisprudence) is of special importance. In this direction, this paper makes an attempt to enlighten many aspects of his personality and explores his scholarly contributions to Islamic sciences with special focus on his works of ╒ ad┘ th literature. It argues that Maul┐ na has significant caliber of ╒ ad┘ th literature and its principles and has touched some important aspects of ╒ ad┘ th. If these manuscripts are edited and published, it will be a good addition to the field. The paper mainly reviews his ╒ ad┘ th works from original manuscript sources that are available in the Maul┐ na └ z┐ d Library of Aligarh Muslim University.